Ethics and Technology in Nursing Education: Rethinking Artificial Intelligence - Canales Morales, Palmira (Investigación y Educación en Enfermería, 2025)
This essay aims to critically reflect on the ethical challenges posed by the incorporation of artificial intelligence (AI) in the education of nursing professionals. Based on an argumentative review of recent scientific literature, three key dimensions are analyzed: personalized learning as an opportunity to promote inclusion and academic autonomy; the potential of AI to reduce educational gaps through public policies that guarantee digital equity; and the strengthening of clinical and ethical judgment through AI-assisted simulations in educational environments. Likewise, the risks associated with its implementation are addressed, such as algorithmic surveillance, the mechanization of moral reasoning, and technological exclusion in contexts with low digital literacy. It is concluded that the real challenge does not lie in the technology itself, but in how it is designed, regulated, and pedagogically integrated in terms of care, dignity, and critical thinking. Finally, the need to advance research that guides regulatory frameworks and educational proposals to ensure an ethical, inclusive, and contextualized integration of AI in nursing education is suggested.